ANALYSIS OF THE ROLE OF THE VILLAGE GOVERNMENT CENTER IN LAMPUNG IN ENHANCING THE CAPACITY OF VILLAGE GOVERNMENT APPARATUS AND VILLAGE COMMUNITY INSTITUTIONS (LKD) - Lina Marya Dewi; M. Oktavianur (International Journal of Multidisciplinary Reseach, 2026)
Various problems in the village include: Villages still lack adequate infrastructure and utilities, both in terms of buildings, information technology facilities, and operational budget support; then the capacity of the apparatus in government administration; management of large village budgets is not supported by qualified human resources; and village government apparatus still has inadequate human resources. The research method used is descriptive qualitative research. This method is used to describe the analysis of the role of Village Government Offices in Lampung in improving the capacity of Village Government Apparatus and Village Community Institutions. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that, through the educational dimension, Village Government Offices contribute to improving the knowledge and skills of village officials and Village Community Institutions. In the facilitative dimension, Village Government Offices function as providers of facilities, mentoring, and learning spaces that support the implementation of village government duties. The consultative dimension strengthens the capacity of village officials and Village Community Institutions to resolve administrative and institutional issues appropriately. The innovative dimension encourages renewal and creativity in village governance and community empowerment.